2010
DOI: 10.1002/elps.200900613
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic computer simulations of electrophoresis: A versatile research and teaching tool

Abstract: Software is available, which simulates all basic electrophoretic systems, including moving boundary electrophoresis, zone electrophoresis, ITP, IEF and EKC, and their combinations under almost exactly the same conditions used in the laboratory. These dynamic models are based upon equations derived from the transport concepts such as electromigration, diffusion, electroosmosis and imposed hydrodynamic buffer flow that are applied to user-specified initial distributions of analytes and electrolytes. They are abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
83
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 200 publications
(378 reference statements)
0
83
0
Order By: Relevance
“…A historical overview together with information on the availability of dynamic simulators is in given in [27] and simulation examples together with a comprehensive list of applications can be found in [28]. The development of new electrophoretic computer models and the use of computer simulation of electrophoretic processes increased significantly during the last few years [17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A historical overview together with information on the availability of dynamic simulators is in given in [27] and simulation examples together with a comprehensive list of applications can be found in [28]. The development of new electrophoretic computer models and the use of computer simulation of electrophoretic processes increased significantly during the last few years [17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The development of new electrophoretic computer models and the use of computer simulation of electrophoretic processes increased significantly during the last few years [17][18][19][20][21][22][23][24][25][26]. Our interest is focused on one-dimensional transient electrophoresis models, which allow high-resolution, real-power simulations for any electrolyte arrangements, including those associated with zone electrophoresis, isotachophoresis (ITP) and isoelectric focusing [27,28]. These models are based on the principles of electroneutrality and conservation of mass and charge and solve equations that are derived from the transport concepts in solution under the influence of a d.c. electric field together with user-supplied conditions, including initial concentration distributions, pKa values, mobilities, column length, column segmentation and current density or voltage applied.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distribution of substances in solution is close to a Gaussian distribution. However, in 2000-2006 (see [11][12][13][14][15][16][17][18]) with the help of numerical simulation of the non-stationary problem, it was revealed that the natural pH-gradients at large intensity of the external electric field in the stationary mode have a step function profile and the distribution of concentration close to rectangular profiles. These results were partially confirmed by experiments.…”
Section: Introductionmentioning
confidence: 99%